Answer:
![\large\boxed{y=\sqrt[3]{x+3}+3}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ed24d11imorouehwufrrz4ngqnmjziatll.png)
Explanation:
f(x) + n - shift the graph n units up
f(x) - n - shift the graph n units down
f(x + n) - shift the graph n units to the left
f(x - n) - shift the graph n units to the right
===========================================
The original graph ( y = ∛x) shifted 3 units to the left and 3 units up.
Therefore, the new equation is:
y = ∛(x + 3) + 3